ANALYSIS OF THE ROLE OF THE BPD (VILLAGE CONSCIOUS BODY) IN VILLAGE GOVERNMENT (CASE STUDY IN LAHUSA SATU VILLAGE): ANALISIS PERAN BPD (BADAN PERMUSYAWARATAN DESA) DALAM PEMERINTAHAN DESA (STUDI KASUS DI DESA LAHUSA SATU) - Annuar Hulu, Dedi (LPPM UPMI, 2024)
This study aims to analyze the role of the Village Consultative Body (BPD) in village governance with a case study in Lahusa Satu Village. BPD is a village institution that has a strategic function in the village governance process, including in formulating village policies, supervising the performance of the village head, and accommodating and channeling community aspirations. The research method used is qualitative with a case study approach. Data were collected through in-depth interviews with BPD members, village heads, and community leaders, as well as direct observation and documentation studies of village regulations, activity reports, and BPD meeting minutes. The results of the study indicate that the BPD of Lahusa Satu Village plays an important role in making village policies and supervising the performance of the village head, but still faces various obstacles such as a lack of understanding of BPD members regarding regulations, minimal resources, and limited technical support. In addition, community participation in village development facilitated by the BPD also showed positive results by increasing a sense of ownership and shared responsibility for village development. In conclusion, to optimize the role of the BPD, it is necessary to increase the capacity of BPD members through training and technical guidance, as well as closer cooperation between the BPD, village head, and the community.